Patriotic songs: A strategic Tool in Hybrid Warfare - Muzammil Saeed; Syed Muhammad Kaleem Bukhari; Dr. Farasat Rasool (JOURNAL OF MEDIA & COMMUNICATION, 2021)
This research intends to examine and analyze the significant strategic tool of hybrid warfare, patriotism, in the songs produced by the ISPR. For this purpose, our study applied quantitative measures to analyze the textual and visual elements of patriotism. To provide a comprehensive detail, regarding the elements of patriotism, this study analyzed videos of the songs by creating 7 textual and 8 visual elements with respect to these two categories. Recently, when Pakistan Army is facing multiple complex challenges of internal and external threats and confrontation, the war across every domain has become obvious in this multifaceted battlefield which support military operations and develop favorable emotions and behavior among the nation, and minimize the negative effects of any loss. Motivation and willingness to sacrifice were found out to be major themes in patriotic songs produced by ISPR along with the focus on sacrifices and efforts of armed forces of Pakistan.